PERANAN KEKUATAN RELATIT OTOT UNTUK BELAJAR JUDO - Jumhan Pida (Jurnal Kependidikan, 1999)
The research is meant to find out the role of muscle's relative strength in judo learning.The method used is descriptive correlation method with path analysis. technique. Cousal models being hypothesized correlate the wi"iables of muscle's relative strength to pull and Push in judo learning. The results are: the form  causal models being hypothesized must be changed by eliminating the pth having coeficient less than 0.05. The pathbetween age and skill mastery of model I and 2, and  tw,een age and combination of skills of mastery and technique application of model 3 and 4 are eliminated. The relatrve strength to pull has dominant role to wards the skill technique mastery and application in the play, and the relatrve strength to pushhas  dominant rolet owards the skill of the technique mastery and application and also the combination of two skills,because the paths among the variables in the new models still exist.